A Comprehensive Evaluation of Perforated Façades for Daylighting and Solar Shading Performance: Effects of Matrix, Thickness and Separation Distance - Doris Abigail Chi Pool (Journal of Daylighting, 2019)
New design tools have enabled architects to explore complex geometries for building envelopes. Perforated Screens (PS) have gained popularity but their design is still intuitive, often focused on aesthetic and morphological criteria. Yet, there is a lack of guidelines or quantitative standards for designing optimal PS, in terms of their daylight provision, views outside, solar shading or energy performance. Since PS can greatly influence the interior conditions, it is essential to understand the effect of screen parameters, such as thickness, perforation percentage, separation distance, and others that are often manipulated by designers. This paper analyses the daylighting and shading performance of thick PS in office buildings. Five design parameters were simultaneously tested in terms of the annual daylight and solar irradiance contribution. Simulations were performed with DIVA-for-Grasshopper and the following metrics were accounted: useful daylight illuminance, actual daylight availability, and shading coefficients. Three orthogonal arrays allowed the selection of 64 PS configurations as representatives. The overall average of every metric was used as an approach to select all factors having a mean significantly different. The mean values were then established as ‘Preferable’ targets. Finally, design guidelines to plan thick PS used in front of South, East, and West glazed façades, in a Mediterranean climate, were proposed. The results highlighted the importance of selecting appropriate values for every design parameter to enhance the integrated performance of thick PS.